"Prison Is for Young People!" Youth, Violence, and the State in Praia and Mindelo, Cape Verde. (September 2016) - Zoettl, Peter Anton
Abstract: In the past decade Cape Verde has seen an unexpected outburst of gang-related urban violence. The state has reacted mainly by means of a repressive securitization policy, which has not been able to offer more than temporary solutions. In public discourses, "broken" families, youth drug consumption, and a supposed lack of education and sufficiently severe punishment are often referred to as the main causes for the rise in crime. The article discusses such discourses, contrasting them with the experiences and narratives of inmates from the country's two central prisons. It suggests that extrajudicial punishment of suspects and offenders by police officers, as reported by many juvenile convicts, is part of the dynamics of violence manifest in different spheres of Cape Verdean society and may be a possible factor influencing the decision of young citizens to "opt" for, or stick to, careers of marginality and delinquency. Résumé: Au cour de la dernière décennie, le Cap-Vert a connu une explosion inattendue de violence urbaine liée aux gangs. L'État a réagi principalement par le biais d'une politique de sécurisations répressive, qui n'a été en mesure que d'offrir des solutions temporaires. Dans les discours publics, familles "brisées, " consommation de drogues chez les jeunes due à un manque supposé d'éducation et des peines suffisamment sévères ont souvent été désignés comme causes principales à l'augmentation de la criminalité. L'article traite de tels discours, les contrastant avec les expériences et les récits des détenus de deux prisons centrales du pays. Il suggère que la peine extrajudiciaire des suspects et des délinquants par des agents de police, tel qu'elle est rapportée par de nombreux mineurs condamnés, fait partie de la dynamique de la violence manifestée dans les différentes sphères de la société Cap-Verdienne et peut-être un facteur possible d'influence dans la décision des jeunes citoyens à "opter" pour et rester fidele aux carrières marginales et de délinquance.